Development of Test and Measurement of Knowledge Level of Sunflower Farmers (Indian Journal of Extension Education, 2022)
A test was constructed to measure the farmers’ knowledge level on sunflower cultivation during 2021-22. Relevant items were collected from review of literature and discussed with scientists. For relevancy test, 39 items were sent to 320 experts for their judgement. Based on 45 experts judgement, 18 items (overall mean score > 2.57) were selected for item analysis and administrated to 60 farmers of Chinnakoduru village of Siddipet district. Item analysis was done by item difficulty index, item discrimination index and point biserial correlation and 15 items were finalized for knowledge test. Reliability (Cronbach alpha, Spearman brown coefficient and Guttman split-half) and validity (point biserial correlation) were estimated for standardization of the test and found to be highly significant. The test was administered to 140 respondents in Andhra Pradesh and Telangana states. In Andhra Pradesh, 78.8 per cent and in Telangana 85.0 per cent of respondents were in medium level of knowledge category. The item analysis indicated significant differences in knowledge level of farmers pertaining to most suitable period of sowing sunflower crop during Rabi, suitable sunflower hybrids, optimum seed rate, critical period of weed competition, application of fertilizers and bee keeping in sunflower in two states.